The Influence of Human Resource Competence and Workload on Employee Performance with Work Motivation as an Intervening Variable at Bank Jakarta, East Jakarta Mayor Office Branch - Anisa Ratna Pradanti; Osly Usman (Journal of Digital Business and Global Economy, 2026)
Employee productivity within a company is shaped by workforce capability, occupational demands, and professional drive. This study aims to elucidate how human resource capability and task load impact personnel output, utilizing professional drive as an intervening variable within Bank Jakarta. Adopting a quantitative approach, five-point Likert scale questionnaires were administered to a sample of 84 staff members, with data subsequently evaluated via Partial Least Squares-Structural Equation Modeling (PLS-SEM). The outcomes demonstrate that both professional capability and operational demands exert a significant, positive influence on staff output and their professional drive. While professional drive fails to intervene in the connection between task load and staff output, individual capability does exhibit an interdependent relationship with productivity, which is fully intervened by professional drive. Ultimately, these insights contribute to theoretical advancement, concurrent task-load optimization strategies, and modern drive-enhancement techniques to elevate workforce output. Both capability and drive are mutually reinforcing components essential for operational efficiency, while strategic task management remains vital for maintaining balanced workforce output.